Effects of protein quantity and type on diet induced thermogenesis in overweight adults: A randomized controlled trial. Issue 4 (August 2019) - Kassis, Amira; Godin, Jean-Philippe; Moille, Sophie E.; Nielsen-Moennoz, Corine; Groulx, Karine; Oguey-Araymon, Sylviane; Praplan, Fabienne; Beaumont, Maurice; Sauser, Julien; Monnard, Irina; Kapp, Anne-France; Ammon-Zufferey, Corinne; et al.
Summary: Background & aims: Protein content of a meal is hypothesized to drive DIT dose-dependently. However, no single meal study exists comparing two different doses of protein on DIT. In addition, the source of protein, particularly whey protein, was shown to have a higher DIT than casein and soy in the acute setting, however the mechanism behind this difference is not yet clear. The aim of the present work is therefore to evaluate the efficacy of two different doses and types of protein (whey protein and casein) on DIT in overweight adults. Methods: Randomized, double blind crossover including seventeen overweight men and women assigned to four isocaloric study treatments where protein and carbohydrate were exchanged: control, 30 g of whey protein microgels (WPM30), 50 g WPM (WPM50) or 50 g micellar casein (MC50). Energy expenditure was measured by indirect calorimetry. Blood, breath and urine samples were collected in order to measure substrate oxidation, amino acid profile, glucose and insulin, protein turnover and other metabolic parameters. Results: DIT was 6.7 ± 3.7%, 13.0 ± 5.0%, 18.0 ± 5.0% and 16.0 ± 5.0% for control, WPM30, WPM50 and MC50, respectively. There was a significant difference between WPM50 and WPM30 (p < 0.005) and a trend was observed between WPM50 and MC50 (p = 0.06). WPM50 resulted in the highest total, essential, and branched-chain plasma amino acid concentrations when compared with the other study treatments (p < 0.005) and a higher insulin concentration than MC50 (p < 0.005). Protein oxidation was higher for WPM50 than MC50. Protein turnover was significantly correlated with DIT through total leucine oxidation (r = 0.52, p = 0.005). Conclusions: Our findings show that DIT does increase at a dose beyond 30 g of WPM and that the type of dairy protein may have an effect on DIT with WPM tending towards a higher DIT than casein. Although further research is required to understand the mechanism behind the effect of different protein sources on thermogenesis, we suggest that amongst the components of protein turnover, protein oxidation may be an important driver of thermogenesis at doses higher than 30 g. These results have concrete implications when choosing a dose of protein to optimize its thermogenic effect. Clinical trial registry number: NCT02303080www.clinicaltrials.gov .